052. Surgical Management of a Tumor Adhering to Ileum and Posterior Stomach: A Case Report - Nugraha, Anshari Dwi (JBN (Jurnal Bedah Nasional), 2024)
Background : Tumors in the transverse colon that invade adjacent organs, such as the ileum and posterior stomach, present complex surgical challenges. Resection and reconstruction are often required to achieve optimal outcomes. We present a case of a large transverse colon tumor adherent to the ileum and posterior gastric wall, managed with extensive surgical resection and reconstruction. Case: A 54-year-old male presented with abdominal pain, bloating, and weight loss. Imaging studies revealed a large mass originating from the transverse colon, adherent to the ileum and posterior gastric wall. Intraoperative findings confirmed the tumor’s adherence to the ileum, approximately 220 cm distal to the ligament of Treitz, as well as its invasion of the posterior gastric wall. The surgical team performed a multi-organ resection. The segment of ileum involved, located 220 cm from the ligament of Treitz, was resected, and an ileo-ileal anastomosis was performed. The primary tumor, located in the middle of the transverse colon, necessitated a total resection of the transverse colon, with subsequent anastomosis between the ascending and descending colon. Additionally, the portion of the posterior stomach adherent to the tumor was removed through subtotal gastrectomy, followed by a Billroth I reconstruction. Postoperatively, the patient recovered well, with no significant complications. Histopathology confirmed the tumor to be a moderately differentiated adenocarcinoma. The patient is currently undergoing adjuvant chemotherapy. Conclusion: This case highlights the complexity of managing tumors with multi-organ involvement. Comprehensive surgical resection, combined with appropriate reconstruction techniques, can result in favorable outcomes. Early detection and aggressive surgical management are essential in cases involving locally advanced tumors with invasion into adjacent structures.